2007
DOI: 10.1111/j.1651-2227.2007.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in children with neurofibromatosis 1

Abstract: Our findings suggest that lumbar- or proximal femur-DEXA, rather than forearm- or total body-DEXA, could reveal significantly decreased BMD in children with NF1, especially in those with skeletal involvement of NF1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 9 publications
10
35
0
Order By: Relevance
“…In our study, the prevalence of NF1 subjects with a very low aBMD (Z-score À2) was similar to those reported in other studies that adopted the same cut-off and carried out on a similar population to that used by ourselves (23,27). A prevalence of osteoporosis of 19%, defined on the basis of a T-score À2.5 was found in NF1 adults by other authors (25,26).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, the prevalence of NF1 subjects with a very low aBMD (Z-score À2) was similar to those reported in other studies that adopted the same cut-off and carried out on a similar population to that used by ourselves (23,27). A prevalence of osteoporosis of 19%, defined on the basis of a T-score À2.5 was found in NF1 adults by other authors (25,26).…”
Section: Discussionsupporting
confidence: 87%
“…In agreement with other recent studies (23) our findings support the usefulness of measuring aBMD at femur in NF1 subjects. Moreover, when facing growing subjects, performing DXA in smaller regions could be preferable to the whole body evaluation because of the lesser irradiation exposure (23). This study in accordance to literature data (2,22,24) suggests that NF1 individuals present a systemic deficiency in aBMD, which transcends the presence of orthopedic defects and developmental bone dysplasias.…”
Section: Discussionsupporting
confidence: 80%
“…Based on the intraoperative findings of poor vertebral bone quality, they measured the BMD of the lumbar spine in 12 young (mean age of 19.1 years) NF1 patients with severe scoliosis requiring surgical correction and found a significant reduction in the BMD (mean z-score = −2.5) at the lumbar spine which was inversely correlated with the severity of scoliosis. Following this initial report, recent studies have confirmed a decreased bone mass in NF1 patients including children [8][9][10][11][12]. Lammert et al performed a cross-sectional study on 104 adults with NF1, using quantitative ultrasonometry (QUS) and found that BMD was significantly lower in NF1 patients than in the normal population and similarly to Illes et al the decrease in BMD appeared to be more pronounced in patients with severe scoliosis [9].…”
Section: Introductionmentioning
confidence: 77%
“…Decreased BMD in both sexes at an early age has been reported in up to 50% of individuals with NF1 [Illes et al, 2001;Kuorilehto et al, 2004b;Lammert et al, 2005;Dulai et al, 2007;Stevenson et al, 2007;Yilmaz et al, 2007;Brunetti-Pierri et al, 2008;Duman et al, 2008]. This may be related to an inadequate increase in bone remodeling observed by both bone histomorphometry and changes in circulating bone markers [Stevenson et al, 2008;Seitz et al, 2009].…”
Section: Osteoporosismentioning
confidence: 99%